Civic Engagement Relawan PKBM Rumah Pintar Punggur Cerdas Dalam Meningkatkan Literasi - Aldi Imanula; Achmadi; Sastra Atmaja, Thomy; Sulistyarini; Zakso, Amrazi (Program Studi PPKn, Fakultas Keguruan dan Ilmu Pendidikan Universitas Buana Perjuangan Karawang, 2023)
This research aims to find out about the civic engagement of Pusat Kegiatan Belajar Masyarakat (PKBM) Rumah Pintar Punggur Cerdas in improving literacy read. Based on the results of this research, the researchers found PKBM volunteers. The PKBM holds a number of programs starting from setting up huts learning, tutoring, digital libraries,reading in the environment, learning english and eradicating illiteracy. Civic engagement volunteers include dedicating themselves as volunteers, collaborating with several parties, providing an understanding of the importance of literacy, and as a mentor in increase literacy. The factors behind volunteers being involded in PKBM Rumah Pintar Punggur Cerdas activities are social factors, self develompment, the same goal, and contributing to society. Obstacles faced by volunteers include obstacles in the field of funding, lack of teaching staff from volunteers, not all volunteers are present during activities, and there are not enough self-confident. Meanwhile, solutions include making donations from fellow volunteers, opening up recruiting volunteers, holding regular evaluations of each activity and taking turns be responsible for the activity. Thus, the actions taken by PKBM Rumah Pintar Punggur Cerdas volunteers are included in civic engagement.